The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/toxsci/kfu014
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Modeling of Early Molecular and Cellular Key Events in the CAR-Mediated Hepatocarcinogenesis Pathway

Abstract: Low-dose extrapolation and dose-related transitions are paramount in the ongoing debate regarding the quantification of cancer risks for nongenotoxic carcinogens. Phenobarbital (PB) is a prototypical nongenotoxic carcinogen that activates the constitutive androstane receptor (CAR) resulting in rodent liver tumors. In this study, male and female CD-1 mice administered dietary PB at 0, 0.15, 1.5, 15, 75, or 150 mg/kg-day for 2 or 7 days to characterize multiple apical and molecular endpoints below, at (∼75 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 67 publications
5
24
0
Order By: Relevance
“…2A), which correlated with hepatomegaly and hepatocellular hypertrophy at both dose levels and increased hepatocellular proliferation at 250 mg/kg/day. In the PB treated animals, Cyp2b1 mRNA was induced in a dose-dependent manner, consistent with CAR activation (Elcombe et al, 2014; Geter et al, 2014); in the low-, mid-, and high-dose groups, Cyp2b1 mRNA was induced 11-, 48-, and 180-fold, respectively (Fig. 2A).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…2A), which correlated with hepatomegaly and hepatocellular hypertrophy at both dose levels and increased hepatocellular proliferation at 250 mg/kg/day. In the PB treated animals, Cyp2b1 mRNA was induced in a dose-dependent manner, consistent with CAR activation (Elcombe et al, 2014; Geter et al, 2014); in the low-, mid-, and high-dose groups, Cyp2b1 mRNA was induced 11-, 48-, and 180-fold, respectively (Fig. 2A).…”
Section: Resultssupporting
confidence: 57%
“…It has been reported that following 7-day exposure to PB, the range of BMD for apical endpoints (e.g. liver weight, hepatic biomarkers, and hepatocyte cell proliferation) in male CD-1 mice was 2.4–30 mg/kg/day (Geter et al, 2014). For CF, the lowest tumorigenic dose is 250 mg/kg/day in rats (Reddy et al, 1979; Sargent et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with previous publications, which suggested similar increases in relative liver weights, hepatomegaly, and hepatocellular hypertrophy following PB and CF exposures (Corton et al, 2014;Elcombe et al, 2014;Miousse et al, 2017). Following oral administration, both PB and CF are rapidly absorbed and transported via the blood, consistent with their pharmaceutical applications (Cayen et al, 1977;Geter et al, 2014). Furthermore, a recent publication has evaluated the in vivo mutagenic response of genotoxic chemicals in a 28-day dosing paradigm at fractions of the carcinogenic dose (Dertinger et al, 2014).…”
Section: Clinical Observations General Toxicity and Target Organ Efsupporting
confidence: 92%
“…29 In a recent study, male and female CD-1 mice were treated with PB at dose levels of 0.15-150 mg kg −1 day −1 for periods of 2 and 7 days. 50 Treatment with PB produced clear dose-dependent effects on a number of key and associative events for the MOA for PB-induced liver tumour formation. Some information on the concordance of dose-response relationships for key and associative events in the MOA for PB-induced tumour formation was observed in a study on the low spontaneous liver tumour incidence C57BL/10 J mouse strain.…”
Section: Experimental Procedures To Derive Data To Support a Car-actimentioning
confidence: 97%
“…For example, PB has been reported to produce liver tumours in CD‐1 mice at a dose level of 75 mg kg −1 day −1 , but not at a dose level of 10 mg kg −1 day −1 . In a recent study, male and female CD‐1 mice were treated with PB at dose levels of 0.15–150 mg kg −1 day −1 for periods of 2 and 7 days . Treatment with PB produced clear dose‐dependent effects on a number of key and associative events for the MOA for PB‐induced liver tumour formation.…”
Section: Experimental Procedures To Derive Data To Support a Car‐actimentioning
confidence: 99%